RETROSPECTIVE STUDY ON THE INFLUENCE OF THE TYPE OF PROSTHETIC MATERIAL ON THE LEVELS OF BONE RESORPTION AROUND DENTAL IMPLANTS - Cosmin Ionuț Lixandru (Romanian Journal of Oral Rehabilitation)
Aim of the study: The aim of the study was to evaluate the influence and impact that types of prosthetic materials can have on levels of bone resorption around dental implants. Materials and methods: This retrospective study was conducted between January 1, 2016 and December 31, 2023 at a private dental clinic in the city of Sibiu, Romania. The realization of the study involved the detailed analysis of the medical records of the patients who came to the clinic during this period of time for complex implanto-prosthetic rehabilitation. The results of this study were obtained by the analysis of a total number of 268 implants. Results: The type of prosthetic material used in complex implanto-prosthetic restorations significantly influences the long-term evolution of this therapy. Zirconium-based restorations were found to report lower levels of bone resorption around dental implants in all planes analyzed. Conclusions Zirconium-based restorations in implant-prosthetic treatment should be chosen whenever the clinical and radiological situation allows it, as they bring a series of important advantages and can contribute to the long-term success of implant-prosthetic rehabilitation.